Profitability Analysis Before and After the Merger in Islamic Banking Companies Listed on the IDX - Nur Nisa SH; Romansyah Sahabuddin; Anwar Rauf; Sahade Sahade (Universitas Negeri Makassar, 2022)
This study aims to analyze the profitability of Islamic banking companies before and after the merger, which is measured using financial ratios. The population used is all financial statements of companies in the Islamic banking sector that have merged and are listed on the Indonesia Stock Exchange (IDX) for 2 years. The research sample was taken using the non-probability sampling method used is saturated sampling, namely in particular the financial reports of BRI Syariah (BRIS), BNI Syariah (BNIS) and Bank Syariah Mandiri (BSM) for the quarterly period of 2020 as well as the financial reports of Bank Syariah Indonesia (BSI) quarterly period in 2021. Data collection was carried out using documentation techniques. Data were analyzed by summarizing financial statements, by calculating profitability ratios using Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE), and comparing ratio calculations from the year before and after the merger, as well as analyzing and interpreting calculation of the three ratios. Based on the results of the study, it was found that the average BOPO ratio of Bank BRI Syariah (BRIS), Bank BNI Syariah (BNIS) and Bank Syariah Mandiri (BSM) before the merger was 80.17%. Meanwhile, in the 2021 period, the average BOPO ratio for Bank Syariah Indonesia (BSI) after the merger is 79.29%. The average ROA ratio for Bank BRI Syariah (BRIS), Bank BNI Syariah (BNIS) and Bank Syariah Mandiri (BSM) before the merger was 1.34%. Meanwhile, in the 2021 period, the average ROA ratio for Bank Syariah Indonesia (BSI) after the merger is 1.63%. The average ROE value of Bank BRI Syariah (BRIS), Bank BNI Syariah (BNIS) and Bank Syariah Mandiri (BSM) before the merger was 10.17%. Meanwhile, in the 2021 period, the average ROE ratio for Bank Syariah Indonesia (BSI) after the merger is 12.62%.